Wie kann schulischer Nachbarsprachenunterricht zum mehrsprachigen Lebens- und Erfahrungsraum werden? Umsetzungsbeispiele für den Polnischunterricht - Lisek, Grzegorz; Putzier, Agnieszka (Glottodidactica, 2024)
Borderlands are special areas, where multilingualism is particularly apparent. As a result, more and more EU-funded projects have set themselves the goal of promoting this idea. This paper focuses on the possibilities for active support of multilingualism based on experiences from three INTERREG-projects (INT2 and INT131), which focus on the Polish-German borderland. On one hand, the topics of the projects concerning emergency communication are still important, on the other hand, the materials which were prepared in the projects regarding learning the neighbour’s language from kindergarten to the final school exam can be used and promoted as verified and well assessed. The goal of our reflections is to present and join the perspectives on teaching languages – education policy and teaching methodologies. The reflections are based on the usage of the materials that are being presented here and seen as a possibility for transfer to other subject areas. Because the classes with speakers of a neighbour’s language need to be holistic, experiential, interdisciplinary and individualised it is important that we look at the materials and methods which were used in the projects. It is important to highlight that creating multilingual spaces for experience and action in school (Polish) lessons is the first step in ensuring that all pupils, regardless of their background, have access to an equitable education.